Area development and policy: an agenda for the 21st century. Issue 1 (2nd January 2016) - Dunford, Michael; Aoyama, Yuko; Campolina Diniz, Clélio; Kundu, Amitabh; Limonov, Leonid; Lin, George; Liu, Weidong; Park, Sam Ock; Turok, Ivan
ABSTRACT: A series of significant recent trends in world development involve transformations taking place at multiple geographical scales. These transformations suggest that there are multiple pathways to development, that these pathways derive from the articulation and interdependence of governance structures/capacity and development models, and that these trends will lead to a radical reshaping of the international economic and political order. Our world remains a world of diverse civilizations whose national, regional urban, rural and local development trajectories require detailed investigation and research from a range of perspectives, including those of emerging economies themselves. International communication and exchange, deriving from these multiple experiences will contribute to inclusive cooperation and mutual learning.